SISTEM WARIS ADAT BILATERAL HAZAIRIN: ANALISIS DALAM LENSA MAQᾹṢID SYARῙ’AH YŪSUF QARAḌᾹWῙ - Istifadah, Nur; Khoirin, Nur (Journal of Islamic Studies and Humanities, 2024)
AbstractOne of Hazairin's thoughts regarding bilateral inheritance law is that the Koran has regulated a system of equality between two different genders. This is what underlies his thinking regarding the distribution of inheritance, where for communities with father-mother clans or a bilateral system, assets to heirs are distributed fairly and according to their rights. Yūsuf al-Qaraḍāwī's maqāṣhid al-syarī'ah thinking is very moderate and adapts to changing times and conditions so that it can be accepted by all groups. The qualitative research method with this type of literature takes data sources from several primary data such as books by Hazairin and books by Yūsuf al-Qaraḍāwī. The data analysis process uses descriptive-analytical analysis, with a maqāṣhid al-syarī'ah approach, in which the writer-researcher will examine Hazairin's thoughts regarding bilateral customary inheritance in the view of maqāṣhid al-syarī'ah Yūsuf al-Qaraḍāwī. The results of this paper show that the inheritance law that has been regulated by Islamic Sharia certainly contains benefits for its creatures, benefits that do not look at gender differences, especially in terms of Islamic inheritance. As expressed by Yūsuf al-Qaraḍāwī, humans need to know and understand religion, not just know religion without understanding it, because with this the meaning and intentions of the Shari'ah can be achieved by humans.Keywords:   Hazairin's Bilateral Heir, Maqāṣhid al-Syarī'ah, Yūsuf al-QaraḍāwīAbstrakSalah satu pemikiran Hazairin mengeni hukum waris secara bilateral yakni bahwasannya al-Qur’an telah mengatur sistem kesetaraan antara dua gender yang berbeda. Hal tersebut yang melandasi pemikirannya terkait pembagian waris, yang mana bagi masyarakat dengan clan/marga ayah-ibu atau disebut  dengan  sistem bilateral, membagikan harta kepada ahli waris dibagikan secara adil dan sesuai dengan haknya. Pemikiran maqāṣhid al-syarī'ah Yūsuf al-Qaraḍāwī sangat moderat serta menyesuaikan dengan perubahan masa dan kondisi, sehingga dapat diterima oleh semua kalangan. Metode penelitian kualitati dengan jenis kepustakaan ini mengambil sumber data dari beberapa data primer seperti buku karya Hazairin dan kitab karya Yūsuf al-Qaraḍāwī. Proses analisis data menggunakan analisis deskriptif-analitis, dengan pendekatan maqāṣhid al-syarī'ah, yang mana penulis-peneliti akan menelaah pemikiran Hazairin terkait dengan waris adat bilateral dalam pandangan maqāṣhid al-syarī'ah Yūsuf al-Qaraḍāwī. Hasil tulisan ini menunjukkan bahwasannya, hukum waris yang telah diatur oleh syari’at Islam sudah tentu mengandung kemashlahatan bagi makhluknya, kemashlahatan yang tidak memandang perbedaan gender khususnya dalam hal waris Islam. Sebagaimana yang diungkapkan oleh Yūsuf al-Qaraḍāwī bahwa pentingnya manusia mengetahui dan memahami agama, bukan hanya mengetahui agama tanpa memahaminya, sebab dengan hal tersebut makna dan maksud-maksud syari’at dapat digapai oleh manusia.Kata kunci:         Waris Bilateral Hazairin, Maqāṣhid al-Syarī'ah, Yūsuf al-Qaraḍāwī